2019
DOI: 10.3389/fimmu.2019.01379
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Lung Tumor Development in ApoE Knockout Mice via Enhancement of TREM-1 Dependent NK Cell Cytotoxicity

Abstract: Apolipoprotein E (ApoE) is known to regulate lipid homeostasis and associated with atherosclerogenesis. Eventhough atherosclerogenesis is associated with tumor development, the role of ApoE in lung tumorigenesis and metastasis is not clear. Thus, the tumor growth and metastasis were compared in WT and ApoE knockout (KO) mice. Urethane-induced lung tumor incidence and B16F10 lung metastasis in ApoE knockout (KO) mice were significantly reduced in comparison to that in WT mice. Knockdown of ApoE expression in lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…APOE is significantly highly expressed in lung cancer, and its overexpression promotes cancer proliferation and migration, and aggressiveness of lung cancer [ 43 ]. APOE knockout inhibits tumor growth and metastasis by increasing REEM-1-mediated infiltration of NK cells in lung cancer [ 44 ]. Notably, APOE modulates brain glucose metabolism in AD [ 45 ], and affects glucose uptake in atherosclerosis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…APOE is significantly highly expressed in lung cancer, and its overexpression promotes cancer proliferation and migration, and aggressiveness of lung cancer [ 43 ]. APOE knockout inhibits tumor growth and metastasis by increasing REEM-1-mediated infiltration of NK cells in lung cancer [ 44 ]. Notably, APOE modulates brain glucose metabolism in AD [ 45 ], and affects glucose uptake in atherosclerosis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Kemp Samantha B et al 10 , orthotopic implantation of mouse pancreatic ductal adenocarcinoma (PDA) cells into syngeneic wild type or in Apoe -/- mice showed reduced tumor growth in Apoe -/- mice. Lee Yong Sun et al 11 found that urethane-induced lung tumor incidence and B16F10 lung metastasis in Apoe -/- mice were significantly reduced in comparison to that in WT mice. Buss Linda A et al 12 reported that Apoe -/- mice also had a reduced rate of metastasis compared to WT mice implanted with EO771 murine breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this molecule has been recently reported to be required for successful NK cell anti-tumor activity in a mouse lung tumor model. Lee et al [245] demonstrated that lung tumor development and metastasis were suppressed via an increase in TREM-1-dependent NK cell cytotoxicity. TREM-1 blockade with LP-17 prevented NK cell killing, whereas TREM-1 mAb recovered NK cytotoxic effects.…”
Section: Discussionmentioning
confidence: 99%